International Students’ Motivation to Study Abroad: An Empirical Study Based on Expectancy-Value Theory and Self-Determination Theory - Yue, Yun; Lu, Jinjin (Frontiers in Psychology, 2022)
Push-pull theory, consumer decision-making models and rational choice theory are commonly used to explain international student mobility (ISM). Despite their merits, the individual’s motivation to study abroad is ignored. Based on two motivation theories— expectancy-value theory (EVT) and self-determination theory (SDT), this study examines whether students’ intention to study abroad originates from the students themselves or compromises social pressure and how the external factors defined in push-pull theory work with these motivations to affect their decision-making. A quantitative study was conducted with a sample size of 736 international students in China. The findings show that the decision to study abroad is a highly subjective and intrinsically driven behaviour in which realising one’s self-worth or fulfilling one’s purpose of life plays the most significant role. Making a decision needs a ‘cost-benefits calculus’, but the utility value of study abroad was positioned behind attainment value and identified motivation. The heterogeneity of international students' motivation was also differentiated by both their gender and their parents’ educational backgrounds